Atypical fibroxanthoma in a young female patient with systemic lupus erythematosus: A case report and literature review - Sze-Wen Ting; Shih-Jyun Yang; Yung-Yi Lee (Wolters Kluwer Medknow Publications, 2018)
A 23-year-old woman presented with an asymptomatic erythematous subcutaneous nodule on her right shin that had been present for the preceding 6 months. She had been diagnosed with systemic lupus erythematosus (SLE) and Sjogren's syndrome 6 years ago and was controlled with prednisolone and hydroxychloroquine. The nodule was excised and the pathologic diagnosis was atypical fibroxanthoma. This case is reported because this tumor occurred in an atypical site in a young female patient with SLE. The occurrence of this unusual atypical fibroxanthoma is believed to be related to altered immunity. Keywords: Atypical fibroxanthoma, Systemic lupus erythematosus